Herramientas digitales para fortalecer el pensamiento lógico matemático en la Educación Inicial - Chanaguano Punina, Janeth Eufemia (2022)
The present project has as its theme; digital tools to strengthen mathematical logical thinking in initial education, the main objective was to design a guide of digital tools to strengthen mathematical reasoning in Initial Education in the "Educational Unit Fourteen of Julio JAE”, with a descriptive design, for this reason eight workshops were worked on in the proposal using digital tools in order to enhance intellectual capacity in children and thus promote a teaching-learning change that encourages pleasure by learn, and your. At the same time, provide meaningful learning to each of the children of the "Educational Unit Fourteen of July - JAE". Technology has become essential today, so it is intended to provide a quality learning process, through technological applications such as YouTube, Blackboard Online, GeoGebra, Genially, Vimeo, Padlet, Powtoon and Canva, through these innovative tools are seeks to ensure that children obtain their quality educational training with the digital resources generated in the workshops. The same ones that were validated with two teachers with a master's degree and three initial education teachers specialized in the subject of this proposal; "I enjoy, I entertain myself and I learn mathematics", which resulted in an assessment of "Fairly well" and "Totally well". The established workshops allow the child to solve simple and complex problems, improve mental agility, encourage interest, and also allow the child to understand and practice mathematical logical thinking processes.